Kepuasan Pernikahan Berhubungan dengan Depresi Pasca Melahirkan - Irma Nurbaeti; Iklil Farida (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between marital satisfaction and postpartum depression in postpartum mothers in South Tangerang. The type of research used is quantitative research with a cross-sectional approach. The results showed that 60 respondents (20.55%) experienced postpartum depression with an EPDS score of more than 13, and 15 respondents (5.16%) were dissatisfied with their marriage. In conclusion, there is a relationship between marital satisfaction and postpartum depression with a p-value of 0.018. Mothers who are dissatisfied with their marriages tend to experience postpartum depression. Keywords: Postpartum depression, Marital satisfaction, Maternal, Nurse